AN ANALYSIS OF CHILDREN PSYCHOLOGICAL VIOLENCE IN THE SLUMDOG MILLIONAIRE MOVIE BY DANNY BOYLE - Rahmatun Islami; Dedi Efendi; Dodi Oktariza (Universitas Muara Bungo, 2018)
This research analyzes about the types of violence, causes and the impacts for violence in the Slumdog Millionaire movie by Danny Boyle. This research uses descriptive qualitative method which is according to Bodgan and Bikle (1982) explain that the collected data which is used this method is in form of words as picture rather than numbers related to Slumdog Millionaire movie. The data is analyzed through some ways: identify, classify, analyze, and conclude. The results of this analysis the writer found 17 types of violence such as physical violence, verbal violence, sexual violence and neglect. Violence received by children results in two cases, positive and negative. Positive which can result in children getting stronger in facing problems and becoming independent. While from the negative side it results in depression,flashback and ect. However the violence was caused by several pressure factors from the social stress and family.The analysis concluded that the movie illustrated the existence of violence. The vargant juvenile had to experinced miserable lives without goverment protection. But in this movie it is also shows that homeless children can also succeed cause to the bad past they have experience.Keywords: Psychological Violence, Slumdog Millionaire.